Hydrophobic modification and durability protection of cotton garment fabric surfaces by graphene oxide/PGMA composite coatings - Xiaoya He; Wenhui Zhou (Scientific Reports)
Abstract Cotton fiber fabric with practicability and functionality attracts much attention and plays an important role in many occasions. However, its surface contains many hydroxyl groups to show a hydrophilicity, leading to easy adhesion to stains to limit the application. In this work, polyglycidyl methacrylate (PGMA) was used as an oily and flexible matrix and graphene oxide (GO) particles were used as a filler. PGMA/GO composite modified fabrics with hydrophobicity, self-cleaning feature and wear resistance were prepared by constructing surface coatings. Compared with original fabric, PGMA/GO composite modified fabric has a surface hydrophobicity attributed to organic oily characteristic of PGMA, and high surface roughness from GO surface enrichment. The reasonable GO content (1 wt%) in composite coating makes the modified fabric exhibit the best overall performance (surface water contact angle of ~ 151.7°; chromatism of ~ 2.4; large water contact angle of ~ 140.2° after 200 surface wear cycles). This work provides an effective method for an industrial production of high-performance waterproof cotton garment fabrics.